Synthesis of a base-stabilized silicon(I)-iron(II) complex for hydroboration of carbonyl compounds - Khoo, Sabrina (2020)
The reaction of the amidinatosilicon(I) dimer [LSi:]2 (1; L = PhC(N tBu)2) with FeBr2 in tetrahydrofuran (THF) at ambient temperature afforded the silicon(I)-iron(II) dimer [LSi(FeBr2·THF)]2 (2) after 40 h. Compound 2 can catalyze hydroboration of aliphatic and aromatic ketone compounds with HBpin in the absence of any strong reducing agent. Mechanistic studies show that complex 2 reacts with ketone compounds to form a zwitterionic intermediate in the first step of catalysis. Subsequent reaction with HBpin affords the corresponding boron esters and then regenerates complex 2.